Scenario Planning as a Tool to Promote Innovation in Regional Development Context - Boo Edgar; Adli Abouzeedan; Thomas Hedner; Mats A. Lundqvist (European Regional Science Association (ERSA), 2010)
Scenario planning is a tool that can be used to project and promote innovation activities in organizations. The more disruptive the innovation is, the more beneficial effects will be expected to come out of utilizing a scenario planning process. This planning approach may be considered when discussing innovation in relation to regional development as well as in respect to the introduction of novel and potentially radical innovations. In this paper, we discuss the utilization of scenario planning to promote innovation in a regional development context. Scenario planning may provide possibilities for creating various alternative but plausible outcomes (scenarios) of the future and may further provide the possibility to examine them in depth. Scenario planning considers the uncertainties and driving forces that may have an impact on the dynamics of regional development. In the paper we discuss the policies and strategies which are required to promote and enhance the application of the scenario planning technique in initiating and sustaining progress and development in the Nordic region.
Keywords: 330; Scenario planning; innovation; regional development; plausible outcomes; regional development